Sistem Pendukung Keputusan Pemilihan Sepeda Lowrider Terbaik Menggunakan Metode Electre - Juprianto Juprianto (STMIK Budi Darma, 2019)
Decision Support System is an interactive system that provides information, modeling and manipulating data. The system is used to help make decisions in situations that are semi-structured and unstructured situations, where no one knows exactly how the decision should be made. Decision Support Systems are more intended to support management in carrying out analytical work in situations that are less structured with unclear criteria. The selection of the best Lowrider bikes greatly determines the final results of the lowrider bicycle contest. For this reason, the organizers of the lowrider bicycle contest contest need to formulate an alternative for choosing the right lowrder bicycle. The definition of ELECTRE (Elimination Et Choix Traduisant la Realite) is one method of determining ranking sequences through pairwise comparisons between alternatives and appropriate criteria. ELECTRE method is one of the effective methods for MADM (Multiple Attribute Decision Making) with qualitative features, so that it can improve the ability to make decisions.